Attenuated P. falciparum Parasite Shows Cytokine Variations in Humanized Mice - Zhang, Lei-lei; Li, Jin-Long; Ji, Ming-Xin; Tian, Dan; Wang, Li-Yan; Chen, Chen; Tian, Miao (Frontiers in Immunology, 2020)
A recently developed humanized mouse has been used to assess the immune response evoked against the isolated attenuated C9 parasite clone (C9-M; carrying a single insertion disrupting the open reading frame (ORF) of PF3D7_1305500) of Plasmodium falciparum. Significant human RBC engraftment was achieved by ameliorating the residual non-adaptive immune response using clodronate-loaded liposome treatment. Controlled reactive professional phagocytic leukocytes in immunodeficient mice allowed for sizeable human blood chimerism and injected huRBCs acted as bona fide host cells for P. falciparum. huRBC-reconstituted immunodeficient mice received infectious challenge with attenuated P. falciparum C9 parasite mutants (C9-M), complemented (C9-C), and wild type (NF54) progenitors to study the role of immune effectors in the clearance of the parasite from mouse circulation. C9-M and NF54 parasites grew and developed in the huRBC-reconstituted humanized NSG mice. Further, the presence of mutant parasites in deep-seated tissues suggests the escape of parasites from the host's immune responses and thus extended the survival of the parasite. Our results suggest an evasion mechanism that may have been employed by the parasite to survive the mouse's residual non-adaptive immune responses. Collectively, our data suggest that huRBCs reconstituted NSG mice infected with attenuated P. falciparum is a valuable tool to explore the role of C9 mutation in the growth and survival of parasite mutants and their response to the host's immune responses. This mouse might help in identifying novel chemotherapeutic targets to develop new anti-malarial drugs.